Efeito da escovação dentária no manchamento de braquetes estéticos cerâmicos - Oliveira, Cibele Braga de [UNESP]; Maia, Luiz Guilherme Martins [UNESP]; Pinto, Ary Dos Santos [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP] (My University, 2014)
Objective: this study aimed to analyze the in vitro effect of brushing on the color stability of ceramic brackets immersed in dye solutions. Materials and Methods: seven ceramic brackets of four commercial brands were tested: two monocrystalline and two polycrystalline. The parameters of color were obtained by spectrophotometer before and after 21 days of immersion of the brackets in coffee, red wine, Coca-Cola, black tea and artificial saliva. Another group of brackets of each brand were also immersed in the same solutions and for an equal time to the previous group, but with intervals of daily brushing performed by a toothbrushing machine (Mavtec). The data were evaluated by analysis of variance, multiple comparison tests for means and Student's t-test. Results: the mean color change of the brackets without brushing ranged from 0.46 to 7.61, while in the group with brushing these means ranged from 0.36 to 2.50. The staining still remained noticeable (change of color greater than 3.7) for all brackets when immersed in black tea. Conclusion: daily brushing helped significantly in the color stability of ceramic brackets, maintaining the color change to levels considered not visible to the human eye, except for the solution of black tea in which the staining remained relevant.

Objetivo: avaliar, in vitro, o efeito da escovação no manchamento de braquetes cerâmicos quando imersos em soluções corantes. Material e Métodos: sete braquetes cerâmicos de incisivo central superior direito de quatro marcas comerciais foram testados: dois monocristalinos e dois policristalinos. Os braquetes foram imersos por 21 dias em soluções de café, vinho tinto, Coca-Cola, chá preto e em saliva artificial. A mensuração da cor inicial e após 21 dias foi realizada por espectrofotômetro de reflectância de acordo com o sistema CIE L*a*b*, e a mudança de cor (∆E*) foi calculada. Outro grupo foi constituído por uma amostra de sete braquetes de cada marca comercial, que foram imersos nas mesmas soluções e no tempo igual ao anterior, porém, com intervalos diários de escovação realizados pela máquina de escovação Mavtec. Os dados obtidos foram avaliados pela análise de variância (Anova), teste de comparação múltipla de médias e teste t de Student. Resultados: as médias do ∆E* do grupo de braquetes sem escovação variaram de 0,46 a 7,61, enquanto que no grupo com escovação essas médias variaram de 0,36 a 2,50, exceto para o Radiance quando imerso no café, e para o chá preto em todos os braquetes, onde o manchamento ainda permaneceu perceptível (∆E* > 3,7). Conclusão: a escovação diária ajudou significativamente na estabilidade de cor dos braquetes cerâmicos, reduzindo a alteração de cor a níveis considerados não visíveis a olho humano, exceto para a solução de chá preto, cujo manchamento permaneceu relevante.
Effect of brushing on color stability of ceramic brackets
Keywords: Orthodontic brackets; Color; Toothbrushing; Braquetes ortodônticos; Cor; Escovação dentária